2020
DOI: 10.1021/acs.organomet.0c00444
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of White Phosphorus by a Cyclic (Alkyl)(Amino)Alumanyl Anion

Abstract: The stable cyclic (alkyl)(amino)alumanyl anion (CAAAl) 3 reacts with white phosphorus (P 4 ) under ambient conditions, in which P 4 is fragmented into a P 1 unit to afford the bis(alumanyl)phosphide 2, demonstrating the direct formation of a P anion from an Al anion. Structural and electronic features of the latter were fully characterized by standard spectroscopic means, X-ray diffraction analysis, and computational studies, which revealed that 2 bears highly polarized Al (δ+) and P (δ−) and relatively short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…They have shown a range of cycloaddition reactions with unsaturated hydrocarbons (e.g., ethylene, 23 cyclooctatetraene, 10 naphthalene, 24 anthracene, 24 tylene, 24 and stilbene 24 ) and have recently been shown to cause the fragmentation of white phosphorus to afford a bimetallic anion containing a P 1 unit. 25 It is noteworthy that many of these reactions and products replicate those previously observed for neutral Al(I) systems A and B. 3−7 Relevant to this study is the ability of the aluminyl anions to undergo oxidative addition of a range of E−H σ-bonds, resulting in the installation of new Al−H and Al−E bonds at an Al(III) center.…”
Section: ■ Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…They have shown a range of cycloaddition reactions with unsaturated hydrocarbons (e.g., ethylene, 23 cyclooctatetraene, 10 naphthalene, 24 anthracene, 24 tylene, 24 and stilbene 24 ) and have recently been shown to cause the fragmentation of white phosphorus to afford a bimetallic anion containing a P 1 unit. 25 It is noteworthy that many of these reactions and products replicate those previously observed for neutral Al(I) systems A and B. 3−7 Relevant to this study is the ability of the aluminyl anions to undergo oxidative addition of a range of E−H σ-bonds, resulting in the installation of new Al−H and Al−E bonds at an Al(III) center.…”
Section: ■ Introductionsupporting
confidence: 74%
“…Aluminyl anions C–H have demonstrated a wide range of reactivity and enabled access to unusual and reactive new classes of compounds, including a family of anions containing Al–E multiple bonds (E = O, , Se, Te, or NR , ) and heterobimetallic systems with Al–M bonds (M = Au, Y, Mg, , or Ca). They have shown a range of cycloaddition reactions with unsaturated hydrocarbons (e.g., ethylene, cyclooctatetraene, naphthalene, anthracene, diphenylacetylene, and stilbene) and have recently been shown to cause the fragmentation of white phosphorus to afford a bimetallic anion containing a P 1 unit . It is noteworthy that many of these reactions and products replicate those previously observed for neutral Al­(I) systems A and B . …”
Section: Introductionsupporting
confidence: 55%
“…Among low-valent Al­(I) species, , it has been recently shown that Al­(I) nucleophiles, so-called alumanyl anions, ,,, exhibit the unique reactivity to produce novel Al-containing complexes. ,, The Aldridge and Goicoechea group and the Coles, Anker, and McMullin group independently reported the formation of Al–chalcogen bonded species by the reactions of Al­(I) anions with the chalcogen sources (N 2 O, Se, Te). These results prompted us to investigate the formation of an Al 2 O three-membered ring system by the reaction of anionic Al species and an oxygen source.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Very recently, Kinjo and co-workers isolated the doubly metallated phosphide IV (Figure 1): complete breakdown of the P 4 cage was achieved using an alkyl amido aluminyl compound, reflecting the highly reactive nature of the Al I reagent in this case. [14] In the current study, we demonstrate the selective, two-and four- electron reduction of P 4 using aluminyl compound 1. The structurally unique P 4 4À complex is shown to react readily with ammonia, yielding phosphine gas.…”
mentioning
confidence: 66%